Aplicação da teoria das cores em ambientes virtuais para arquitetura e design de interiores - Tavares, Angélica Pereira Marsicano (2007)
The daily of the Architecture and, in special, of the Interior Design, involves untiring learning to relate people to environments, i.e., the establishment of a direct interconnection between the conceptual principles of the projected space (what it is, which is its function and to who it destines) and the plastic conditions (aesthetic) and comfort, necessary to a man for its permanence in the place. To reach this goal, students and professionals of this area need to see, with another people eyes, moved, not only by the art or a refined aesthetic sense, but for the conscience of the colors in its tonalities, combinations, details and chosen compositions have objective functions to fulfill. The color is, after all, one of the main resources of fortifying the concept, the aesthetic and even the environment function. The use of programs like as AutoCAD and 3D Studio, in the creation of architectural or interiors projects, through its precision and possibility of creation of three-dimensional models with quality offers a better accompaniment of the projects for the designer and its customer as well. However, with the technological advances in the Computer Science area and Virtual Reality has been possible the accomplishment of a virtual stroll through the environment and, in such a way, to get visually superior perceivable information in relation to the conventional presentation. In this way, this research dedicates to the development of a computational tool that uses the Virtual Reality for colors application, approaching its Theory, in personalized environments, guaranteeing the visualization, the navigation and the interaction with projects, foreseeing its execution. Moreover, it can be used as a pedagogical support tool and an alternative for assimilation of theoretical colors concepts as well. Furthermore, promotes the approach between designer and his customers through interactive and dynamic experimentations of the environment projected.